2009
DOI: 10.1007/s00339-009-5276-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of interface structure and magnetic properties of Co on Si (100) by surfactant (Sb) mediated growth

Abstract: In this study thin Co films were grown on Si (100): (1) with one monolayer of Sb as surfactant and (2) without any surfactant. The Co film, its interface with the Si substrate and the behavior of the Sb surfactant layer were investigated during the growth by high-resolution Rutherford backscattering. By the use of Sb, the evaporated cobalt grows in a layer-by-layer mode and the mixing of Co and Si at the interface is strongly reduced. During the evaporation of Co, Sb floats on the surface for all Co coverages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The obtained result is found to be in reasonable agreement with the experimental results reported in Refs. [12][13][14][15]. and by us.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The obtained result is found to be in reasonable agreement with the experimental results reported in Refs. [12][13][14][15]. and by us.…”
Section: Resultsmentioning
confidence: 85%
“…The applications of cobalt thin films include, for example, spintronic devices, such as spin valves, magnetic tunnel junctions and magnetic random access memories, microelectromechanical systems, and logic devices and circuits [14][15][16][17]. Recently, thin Co films have been also used to investigate small and isolated skyrmions [18] which presence can be associated with logical one state and in consequence used to construct novel memories [19].…”
Section: Introductionmentioning
confidence: 99%
“…For higher coverage various silicide phases start to grow at the surface, but no pure Co film, even at the highest coverage (2.93 ML of Co) is investigated in this study. In order to reduce the in-diffusion of Co and the outdiffusion of Si and to enhance the growth of layers of pure Co two ways were followed in two subsequent investigations: (a) Co deposition was done while keeping the substrate at lower temperature, -60 • C [17]; (b) a thin layer of surfactant (1 ML of Sb) was used to reduce the amount of out-diffusion of Si to the surface during Co deposition [18]. Both techniques were helpful to reduce the silicide formation to some extent but could not stop it in total.…”
Section: The Direct Co-si (100) (Schottky) Interfacementioning
confidence: 99%
“…In this way they give information about the sharpness of the interface and the homogeneity of the Co and MgO thin films and allow in particular identifying various types of cobalt silicides as a function of depth. The data on the Co-Si Schottky interface have been published before in three publications [16][17][18] and are here summarized in a comparative way. The data on the MgO tunnel barrier are new.…”
Section: Introductionmentioning
confidence: 99%
“…(c alues for polycrystalline case) have been used in different types of multilayers. 3,25,[31][32][33][34][35] It has been demonstrated that surfactant floats at the surface balancing the c of the elements, suppress surface diffusion and prevents island formation. 18,[36][37][38][39][40] To act as a good surfactant an element must have relatively smaller c and larger volume which promotes layer by layer growth and inhibits its incorporation.…”
Section: Introductionmentioning
confidence: 99%